Modality Markers in Visual Mak Yong Traditional Dance Drama - T. Silvana Sinar; Khairani; Suraiya Chapakiya (LingPoet: Journal of Linguistics and Literary Research, 2022)
This study aims at studying the modality markers represented in the selected images of Mak Yong traditional dance drama. Two images were selected through a documentation technique. The analysis results showed the multimodal perspective of modality markers varied from low to high modality. The color saturation, differentiation, and modulation showed the low modality of colors, monochromic due to the limitation of colours ranging from black and white. In accompanying these three mentioned concepts, the contextualization and background appear medium to high modality. It is proved by the detailed background of the images and the illumination of the complete representation of the play of light and shade, and the maximal deep perspective of Mak Yong and Pak Yong’s performance. Since the images are printed monochromic, the representation did not portray the actual colors in reality.